STRATEGI PENERAPAN ELEMEN DESAIN KOMUNIKASI VISUAL DALAMMEMBANGUN CITRA BRAND DIGITAL, STUDI KASUS @Tndon_Id - Muhammad Angga; Muhamad Fikri (STKIP Pesisir Selatan, 2026)
This study aims to analyze the strategy of implementing visual communication design elements in building a digital brand image on the Instagram account @tndon_id. The research employs a descriptive qualitative approach with a single case study method to provide an in-depth understanding of visual practices in a real-world context. Data were collected through visual observation of feed content, interviews with account managers, and supporting documentation, then analyzed using visual communication design principles such as color, typography, illustration, and layout. The findings reveal that @tndon_id applies visual communication design strategically and consistently as a communication system rather than merely an aesthetic element. Strong visual consistency contributes to the formation of a recognizable brand identity and enhances perceptions of professionalism and credibility among audiences. Furthermore, the implementation of clear typographic hierarchy, visual storytelling through illustrations, and structured layout patterns effectively supports fast and clear message delivery, aligning with the characteristics of social media audiences. Content segmentation with distinct yet integrated visual styles also plays a key role in maintaining both consistency and flexibility. These findings highlight that visual communication design serves as a crucial strategic instrument in building a strong digital brand image, particularly on dynamic social media platforms.